The Relationship of School Discipline with Bullying Behavior At SMP N 26 Padang - Amallia Dinung Anggraini; Mursyid Ridha (Universitas Negeri Padang, 2021)
Bullying behavior in the school environment can create an atmosphere that is less supportive of student development, both in the academic and social fields. Bullying is an act of violence that is carried out physically, verbally, socially or cyber bullying which hurts other students, usually affects people who are weak. One of the causes of bullying is rigid discipline. This study aims to see a picture of student bullying behavior, school discipline, and to examine the relationship between school discipline and bullying behavior. The research method used is a quantitative method with descriptive and correlational approaches. The study population was students of SMP Negeri 26 Padang, amounting to 502 students, with a sample of 223 students who were selected by simple random sampling technique. Data collection using the Likert scale model instrument. To see the relationship between the two variables using Pearson Correlation Product Moment. The results of this study found: 1) School discipline was in the medium category with a percentage of 45.3%, 2) the majority of students' bullying behavior was in the moderate category with a percentage of 49.8% 3) there was a significant negative relationship between school discipline and bullying behavior with rxy = - 0.498 and a significant level of 0.000. These results indicate that the majority of students at SMP Negeri 26 Padang have moderate school discipline and the majority have moderate bullying behavior.